Regulating conversion of agricultural land to non-agricultural uses in Negros Occidental issues and problems. - Martir, Karla May O.; Uyaco, Abegail M. (2002.)
This study aims to dsicuss the issues and problems regarding the procedures and measures adopted by the Philippine government to regulate conversion of agricultural land to non-agricultural uses. The study finds that there exist certain barriers to the effective implementation of the land use conversion and land reclassification policies in Negros Occidental. these barriers include lack of information, lack of funds, difficulties in the monitoring processes related to the procurement of approval of application for conversion and decision making with regards to the approval or disapproval of applications for conversion, the machinations of landowners/developers to avoid or reduce the paymentof disturbance compensation to the affected farmers/tiller-occupants. The root of the land conversion problem, however, is the prolonged implementation of the agrarian reform program.
Research Paper (Undergraduate, Bachelor of Science in Economics-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Agricultural lang -- Negros Occidental